2023
DOI: 10.3847/2041-8213/acca83
|View full text |Cite
|
Sign up to set email alerts
|

GRB 211211A: A Neutron Star–White Dwarf Merger?

Abstract: The gamma-ray burst GRB 211211A and its associated kilonova-like emission were reported recently. A significant difference between this association event and GRB 170817A/AT 2017gfo is that GRB 211211A has a very long duration. In this Letter, we show that this association event may arise from a neutron star–white dwarf (NS–WD) merger if the central engine leaves a magnetar behind. Within the NS–WD merger, the main burst of GRB 211211A could be produced by magnetic bubble eruptions from toroidal magnetic field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 124 publications
(154 reference statements)
1
19
0
Order By: Relevance
“…With both ρ 0,GRB211211A and ρ NS−WD (beamed), one can estimate the fraction of NS-WD mergers that indeed make GRBs, i.e., With an N ∼ a few, one can see that f is a very small value, suggesting that only a small fraction of NS-WD systems are capable of producing GRBs (Yang et al 2022). This finding is in agreement with the calculation in Zhong et al (2023).…”
Section: How Rare Is Grb 211211a?supporting
confidence: 93%
See 1 more Smart Citation
“…With both ρ 0,GRB211211A and ρ NS−WD (beamed), one can estimate the fraction of NS-WD mergers that indeed make GRBs, i.e., With an N ∼ a few, one can see that f is a very small value, suggesting that only a small fraction of NS-WD systems are capable of producing GRBs (Yang et al 2022). This finding is in agreement with the calculation in Zhong et al (2023).…”
Section: How Rare Is Grb 211211a?supporting
confidence: 93%
“…Yang et al (2022) pointed out that a neutron starwhite dwarf (NS-WD) merger involving a massive WD component near the Chandrasekhar limit and a similarly massive NS component is self-consistent with all the observations, ranging from prompt gamma-rays and early X-ray afterglow to the engine-fed kilonova emission. This scenario is supported by a more detailed modeling by Zhong et al (2023). We noticed that the scenario involving an NS-WD merger was not included in the analysis by Kunert et al (2023), which only compared the BNS merger, NS-BH merger, core-collapse supernova, and collapsar scenarios.…”
Section: Introductionmentioning
confidence: 79%
“…In particular, simulations show that no r-process material is produced [179], and so we should not expect the very red emission. Although there are suggestions that GRB 211211A could have been produced by a WD-NS merger [19,59], it is unclear if these could readily explain the detailed spectrophotometric evolution of GRB 230307A.…”
Section: Grb 230307a As a White-dwarf -Neutron Star Mergermentioning
confidence: 99%
“…In particular, the natural timescales for emission in compact object mergers are much shorter than the measured duration of GRB 230307A. Previously suggested models that may also explain GRB 230307A include magnetars [55,56], black hole -neutron star mergers [57,58], or even neutron star -white dwarf systems [19,59]. Recent results have also shown that the jet timescale does not directly track the accretion timescale in compact object mergers, and that long GRBs may be created from very short lived engines [60], and hence from binary neutron star mergers without magnetars.…”
mentioning
confidence: 99%
“…On the other hand, Zhu et al (2022) reported the fallback signatures in GRB 211211A, suggesting an NS-BH merger origin. Recent studies by Zhong et al (2023) claim that GRB 211211A could arise from an NS-WD merger if it produces a magnetar as remnant. They argue that the optical afterglows, along with KN-like emission, can be well modeled by combining the standard forward shock with the radioactive decay power of 56 Ni adding a rotational power input from the post-merger magnetar.…”
Section: Introductionmentioning
confidence: 99%